Hepatoprotective effect of curcumin versus silymarin on paracetamol induced hepatotoxicity in rats - REHAM E. MASOUD, (International Journal of Pharma and Bio Sciences, 2017)
Paracetamol is widely used as analgesic-antipyretic leads to liver dysfunction. Silymarin has a hepatoprotective, immunomodulator, anti-inflammatory, antioxidant, and antifibrotic activities. Curcumin suppresses inflammation by reducing levels of inflammatory cytokines and has antioxidant effect. This study assessed the probable protective effect of curcumin against liver dysfunction and compare it to a hepatoprotective agent, Silymarin. The study groups included: normal control, paracetamol treated group (400mg/kg),silymarin (200mg/kg) + paracetamol treated group, curcumin (400mg/kg)+paracetamol treated group. After sacrifice ,plasmatic levels of liver function markers: alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) of all groups, were determined. Bilirubin and total bilirubin were measured. Liver injury was assessed using histological studies. Samples of their livers were then used to determine glutathione level. There was a significant increase (p < 0.05 )in liver markers in paracetamol treated group compared to normal and treated group. Curcumin treated group showed nonsignificant difference compared to Silymarin treated group. Curcumin treated group showed sidnificant increase in liver glutathione level. Both groups showed marked improvement in liver architecture as compared to paracetamol treated group.The available evidences in this study suggest that the complementary effects of silymarin or Curcmin proved to be capable of ameliorating probable-mediated hepatic oxidative damage and the probable mechanism is via antioxidative action.